Identifying creditworthiness criterions and financing approval process of Islamic banks in Indonesia - Muhammad, Imaduddin; Sharofiddin, Ashurov (2020)
Providing financing facility by the bank depends on eligibility and creditworthiness. Creditworthiness is defined as how the banks determine the default probability and how worthy the potential clients to receive the credit facility (Feder et al, 1985 & Corazza et al, 2014). In assessing the risk and quality of the potential clients, the concepts of 5C’s of credit appraisal are often employed (Motti et al, 2012). The 5Cs elements are Character, Capacity, Collateral, Capital, and Condition. Islamic banking has been developing significantly in Indonesia since the first inception in 1991. As of 30 April 2020, there are 14 Islamic banks, 20 Islamic windows and 163 Islamic rural banks (Financial Service Authority, April 2020). It is represented 6.07% of the national banking size in the country. One of the important segments as a backbone in developing Islamic banking in Indonesia is the corporate and commercial banking segment. From the total financing exposure of Islamic banks and Islamic windows of IDR 332 trillion (eqv. USD 22 billion) as of 30 April 2020, 33.49% are in the corporate and commercial portfolio. It is very interesting to explore what is the consideration for Islamic banks in providing financing approval of corporate and commercial clients.